Kemampuan berpikir kritis siswa dalam menyelesaikan soal higher order thinking skills pada kelas v materi ipa - Puspitasari, Ellen; Saputri, Dwi Yuniasih (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
This study examines class 5 students' critical thinking skills in solving Higher OrderThinking Skills (HOTS) questions on food chain materials for science learning (theme 5,subtheme 3). The research was conducted at SDN Mangkubumen Lor No. 15 Surakarta in class 5. Data collection techniques used were tests, interviews and document study. The validity test technique used was the Gregory technique, which consulted with experts in related material (expert judgment). The results of the analysis showed that the percentage of students' critical thinking ability was 74.25%. It is concluded that the ability to think critically of class 5 students at SDN Mangkubumen Lor No. 15 Surakarta is included in the high category. By identifying several critical thinking indicators such as analyzing, inferring, evaluating, and interpreting, critical thinking ability can be identified. Each critical thinking indicators were analyzed to find the percentage. The percentage of the analyzing indicator was 71.6%, the inferring indicator was 72.9%, the evaluating indicator was 77.7%, and the interpreting indicator aspect was 74.8%, and all of the indicators were in the high category. The HOTS questions application to measure critical thinking skills can be said to be successful and indirectly can make students think critically in solving problems.